The Polish Portrait of Bonnie Prince Charlie - Frost, Robert I. author. aut Link
XVI, 135 p. 29 illus., 25 illus. in color.
Keywords: This book is a study of an eighteenth-century portrait of a youth in Polish dress, owned by the National Portrait Gallery in London since 1922, but never publicly displayed. Two inscriptions claim that it is a portrait of Charles Edward Stuart, popularly known as ‘Bonnie Prince Charlie’. The Gallery has always doubted its authenticity and leading experts on Stuart portraiture have dismissed the identification. This study, by a historian of Poland-Lithuania, is the first detailed attempt to research the painting properly. Based on archival sources, it examines its provenance and the connections of its first known owner with the Kinlochmoidart MacDonalds, who fought for the Prince in the 1745 Jacobite Rebellion. It considers a considerable body of evidence to suggest that it is very possible that the portrait is indeed a genuine depiction of the Prince. Robert I. Frost was educated at the University of St Andrews, the Jagiellonian University, Cracow, and the University of London, where he wrote his doctoral thesis. He is a historian of Poland-Lithuania, who has also published on the history of Scandinavia. .